METHODOLOGY FOR APPLYING INTERACTIVE LEARNING IN THE EDUCATIONAL SPACE OF SCHOOL, PROBLEMS AND PROSPECTS (Journal of Universal Science Research, 2023)
The article introduces the methodology of interactive learning; the issues of equipping schools with interactive learning tools are considered.